Estudo da perda de carga e calor no poço injetor no processo De drenagem gravitacional assistida por vapor (SAGD) - Fernandes, Glydianne Mara Diógenes (2011)
The oil companies in the area in general are looking for new technologies that can increase the recovery factor of oil contained in reservoirs. These investments are mainly aimed at reducing the costs of projects which are high. Steam injection is one of these special methods of recovery in which steam is injected into the reservoir in order to reduce the viscosity of the oil and make it more mobile. The process assisted gravity drainage steam (SAGD) using steam injection in its mechanism, as well as two parallel horizontal wells. In this process steam is injected through the horizontal injection well, then a vapor chamber is formed by heating the oil in the reservoir and, by the action of gravitational forces, this oil is drained down to where the production well. This study aims to analyze the influence of pressure drop and heat along the injection well in the SAGD process. Numerical simulations were performed using the thermal simulator STARS of CMG (Computer Modeling Group). The parameters studied were the thermal conductivity of the formation, the flow of steam injection, the inner diameter of the column, the steam quality and temperature. A factorial design was used to verify the influence of the parameters studied in the recovery factor. We also analyzed different injection flow rates for the model with pressure drop and no pressure drop, as well as different maximum flow rates of oil production. Finally, we performed an economic analysis of the two models in order to check the profitability of the projects studied. The results showed that the pressure drop in injection well have a significant influence on the SAGD process.